Persistent T cell-mediated immune responses against Omicron variants after the third COVID-19 mRNA vaccine dose - Milja Belik; Oona Liedes; Saimi Vara; Anu Haveri; Sakari Pöysti; Sakari Pöysti; Pekka Kolehmainen; Sari Maljanen; Moona Huttunen; Arttu Reinholm; Rickard Lundberg; Marika Skön; et al. (Frontiers in Immunology, 2023)
IntroductionThe prime-boost COVID-19 mRNA vaccination strategy has proven to be effective against severe COVID-19 disease and death. However, concerns have been raised due to decreasing neutralizing antibody levels after COVID-19 vaccination and due to the emergence of new immuno-evasive SARS-CoV-2 variants that may require additional booster vaccinations.MethodsIn this study, we analyzed the humoral and cell-mediated immune responses against the Omicron BA.1 and BA.2 subvariants in Finnish healthcare workers (HCWs) vaccinated with three doses of COVID-19 mRNA vaccines. We used enzyme immunoassay and microneutralization test to analyze the levels of SARS-CoV-2 specific IgG antibodies in the sera of the vaccinees and the in vitro neutralization capacity of the sera. Activation induced marker assay together with flow cytometry and extracellular cytokine analysis was used to determine responses in SARS-CoV-2 spike protein stimulated PBMCs.ResultsHere we show that within the HCWs, the third mRNA vaccine dose recalls both humoral and T cell-mediated immune responses and induces high levels of neutralizing antibodies against Omicron BA.1 and BA.2 variants. Three weeks after the third vaccine dose, SARS-CoV-2 wild type spike protein-specific CD4+ and CD8+ T cells are observed in 82% and 71% of HCWs, respectively, and the T cells cross-recognize both Omicron BA.1 and BA.2 spike peptides. Although the levels of neutralizing antibodies against Omicron BA.1 and BA.2 decline 2.5 to 3.8-fold three months after the third dose, memory CD4+ T cell responses are maintained for at least eight months post the second dose and three months post the third vaccine dose.DiscussionWe show that after the administration of the third mRNA vaccine dose the levels of both humoral and cell-mediated immune responses are effectively activated, and the levels of the spike-specific antibodies are further elevated compared to the levels after the second vaccine dose. Even though at three months after the third vaccine dose antibody levels in sera decrease at a similar rate as after the second vaccine dose, the levels of spike-specific CD4+ and CD8+ T cells remain relatively stable. Additionally, the T cells retain efficiency in cross-recognizing spike protein peptide pools derived from Omicron BA.1 and BA.2 subvariants. Altogether our results suggest durable cellmediated immunity and protection against SARS-CoV-2.